Ruang Laktasi Kantor yang Inovatif: Upaya Mewujudkan Kesetaraan dan Inklusivitas Gender di Tempat Kerja Indonesia - Riza Septriani Dewi (Fakultas Seni Rupa dan Desain ITB, 2026)
Working mothers often face challenges at work due to the lack of adequate, comfortable, and standardized breast pumping facilities, forcing them to express milk in unsuitable places like bathrooms, storage rooms, or under desks. This research explores the adaptation of traditional lactation rooms into lactation pods in Indonesian office settings, focusing on mothers returning to work after maternity leave. Using a user-centered design approach, this qualitative study aims to promote understanding and serve as a medium for advocating gender equality in the workplace. The research highlights the importance of creating an inclusive environment for female employees and empowering women at work. The outcome is a conceptual design (CD) that offers a sustainable solution to support breastfeeding-friendly offices while enhancing the productivity of working mothers.